2013
DOI: 10.1039/c2ta00957a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of PtCu3 bimetallic nanoparticles as oxygen reduction catalysts via a sonochemical method

Abstract: We report a sonochemical synthesis of homogeneous PtCu 3 nanoparticles. Ultra-sonication during reduction in a non-aqueous solution is compared with synthesis under identical conditions in the absence of sonication (to form a Rieke alloy). X-ray diffraction (XRD) measurements suggest that the sonochemical procedure produces an amorphous, uniformly alloyed nanomaterial having a composition consistent with the PtCu 3 stoichiometry, while the Rieke alloy is polyphasic. Energy dispersive X-ray (EDX) analysis indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 62 publications
0
41
0
Order By: Relevance
“…Doubek et al reported an ECSA of ≈20 m 2 Ptg −1 for nanoporous nanorods, [12] Gumeci et al ≈20-30 m 2 Ptg −1 for sonochemically prepared nanoparticles, [41] Kolla and Smirnova Adv. Doubek et al reported an ECSA of ≈20 m 2 Ptg −1 for nanoporous nanorods, [12] Gumeci et al ≈20-30 m 2 Ptg −1 for sonochemically prepared nanoparticles, [41] Kolla and Smirnova Adv.…”
Section: Orrmentioning
confidence: 99%
See 2 more Smart Citations
“…Doubek et al reported an ECSA of ≈20 m 2 Ptg −1 for nanoporous nanorods, [12] Gumeci et al ≈20-30 m 2 Ptg −1 for sonochemically prepared nanoparticles, [41] Kolla and Smirnova Adv. Doubek et al reported an ECSA of ≈20 m 2 Ptg −1 for nanoporous nanorods, [12] Gumeci et al ≈20-30 m 2 Ptg −1 for sonochemically prepared nanoparticles, [41] Kolla and Smirnova Adv.…”
Section: Orrmentioning
confidence: 99%
“…Doubek et al reported an ECSA of ≈20 m 2 Ptg −1 for nanoporous nanorods, [12] Gumeci et al ≈20-30 m 2 Ptg −1 for sonochemically prepared nanoparticles, [41] Kolla and Smirnova Adv. a) Reported values of onset potential and current density for ORR in RDE experiments from references, a (PdCuSi), [125] b (Pd-NiB/C), [55] c (Ni59Nb40PtxM1-x (M = Ru, Sn)), [126] d (Pt 42.5 Cu 27 Ni 9.5 P 21 ), [12] e (PtCu 3 ), [41] f (PtIrCo/C), [57] g (AgCu). 2019, 31, 1802120 Figure 13.…”
Section: Orrmentioning
confidence: 99%
See 1 more Smart Citation
“…A home-made reversible hydrogen electrode (RHE) was used as a reference electrode. 22,23 Prior to each experiment, a glassy carbon electrode was polished to a mirror finish using a 0.05 μm alumina suspension, followed by rinsing with ultrapure water to remove alumina particles from the surface. Fe-N-C catalyst ink was prepared by ultrasonically (Misonix, Sonicator 3000) mixing 4 mg of catalyst powder in 150 μL ethanol and 50 μL ionomer (5 wt %).…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…5 The Pt "shell" could be in different forms, like: a Pt-rich surface layer by electrochemical de-alloying 20 or annealing 21 or acid leaching; 14 a Pt overlayer by seedbased chemical reduction;…”
mentioning
confidence: 99%